A real-time high-precision localization algorithm for wireless sensor networks - Wen Ouyang; Ying Tsao (2009 IEEE 6th International Conference on Mobile Adhoc and Sensor Systems, 2009)
Besides sensing the environment variables, the application of localization in wireless sensor networks has became an important research subject. Unlike the other range-free localization schemes which are not effective in real time performance, we propose a real time algorithm, which determines the location of the moving object based on dynamically changing signal strength. The simulation results demonstrated our algorithm is more effective and precise in the sense of real time localization scheme compared with previous method.